Menanti Reformasi Iklim Bisnis di Indonesia - Mudrajad Kuncoro (Universitas Islam Indonesia, 2005)
This paper attempts to explore to what extent the current regime has changed the business and investment climate in Indonesia. Tsunami and earthquake in various regions overshadowed and sank the hope of fundamental changes by what is called as one hundred day of SBY-JK. Our findings illuminate that the SBY-JK regime has not addressed some critical problems encountered by industries and companies thoroughly. Therefore, we argue some suggested corrective actions based the surveys are badly needed for the new cabinet and local governments in Indonesia. The major reforms may include: (1) changing source of economic growth, from consumption driven to investment/ export-led growth; (2) some corrective actions to eliminate, at least reduce, the barriers along roads, seaports, and customs to increase export and eliminate corruption; (3) a well designed and comprehensive medium term planning to highlight the pathways that both central and local government will pursue.